PENGEMBANGAN MODEL PEMBELAJARAN MATEMATIKA SMP KELAS VII BERBASIS KEHIDUPAN MASYARAKAT JAWARA (JAWA DAN MADURA) DI KABUPATEN JEMBER - Abi Suwito; Dinawati Trapsilasiwi (Universitas PGRI Madiun, 2016)
This research is meant to develop innovative teaching equipment which able to improve as well as conserve the culture through Mathematics learning. Learning equipment which is developed are in the form of students’ book and LKS (Student’s Work Book) of Mathematics subject of VIIth grade concerning with the culture of Javanese and Maduries who lives in Jember district. This developmental study is planned in three steos, namely; theorethical study and needs analysis, formulation of learning equipments, as well as testing the equipments and eksperiment. The Model used in this research is developmental model of ADDIE, which divided into 5 phases, namely; Analysing, Designing, Developing, Implementing and Evalualing. The subject of this research are three students of VII grade of SMP (Junior High School). The product of this research is students book which based on Javanese and Maduries culture. The result of this research shows that students’ learning test in Squares subject based on Javanese and Maduries culture are good, with rate of 83,33. It can be conclude that students’ book of VII SMP which based on Javanese and Maduries culture in Squares Shapes material are effective to be used in teaching.